Overcoming Academic Challenges in the United States (Comparative & International Education Series, 2022)
I am from a tiny island in Southeast Asia called Timor-Leste. Timor-Leste recently won its independence in 2002, when I was 7 years old. Born and raised in a country that I am older than, it is hard to even understand what a dream is. However, as life continues to move forward, we learn every day. After graduating from high school in Timor-Leste, I was brave and confident enough to push myself to work long days and nights to apply for a scholarship to study abroad. Hence, in 2015, I was awarded a United States Timor-Leste Scholarship to complete my undergraduate studies at the University of Arkansas